Rural influences on the social network dynamics of district nursing services: A qualitative meta‐synthesis - Jack Gillham; Ivaylo Vassilev; Rebecca Band (Health Science Reports, 2021)
Abstract Background and Aims As demands on healthcare services grow, fiscal restrictions place increased emphasis on services outside of traditional healthcare settings. Previous research into long‐term‐conditions suggests that social network members (including weaker ties such as acquaintances, community groups, and healthcare professionals) play a key role in illness management. There is limited knowledge about the engagement of social networks in supporting people who are receiving medical interventions at home. This qualitative metasynthesis explores the work and the interactions between district nurses (DN) and informal network members supporting people who are receiving medical interventions at home and living in rural areas. Methods A search was undertaken on CINAHL, Medline, and PsychINFO for qualitative research articles from 2009 to 2019. Studies that examined DN in rural locations and/or social network support in rural locations were eligible. Fourteen articles were selected. Results Thematic analysis of results and discussion data from the studies resulted in four themes being developed: the development of both transactional and friend‐like nurse‐patient ties in rural localities, engagement of the wider network in the delivery of good care, blurring of professional boundaries in close community relationships, and issues accessing and navigating formal and informal support in the context of diminishing resources in rural areas. These findings suggest that DNs in rural localities work beyond professional specialties and experience to provide emotional support, help with daily tasks, and build links to communities. There was also evidence that nurses embedded within rural localities developed friend‐like relationships with patients, and negotiated with existing support networks and communities to find support for the patient. Conclusions Findings indicated that developing strong links with patients and members of their networks does not automatically translate into positive outcomes for patients, and can be unsustainable, burdensome, and disruptive. DNs developing weak ties with patients and building awareness of the structure of individual networks and local sources of support offers avenues for sustainable and tailored community‐based nursing support.